1997
DOI: 10.1038/sj.leu.2400549
|View full text |Cite
|
Sign up to set email alerts
|

Human herpes virus 8 (Kaposi’s sarcoma herpes virus) and malignant lymphoproliferations in France: a molecular study of 250 cases including two AIDS-associated body cavity based lymphomas

Abstract: ( Table 1). This series include 126 leukemias and 124 lym-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
72
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 10 publications
0
72
0
Order By: Relevance
“…5,6 Recently, PEL has been recognized as a unique lymphoma entity based on its distinctive features which include presentation as lymphomatous effusion in the serous body cavities and consistent infection of the tumor clone by human herpesvirus type 8 (HHV-8). [1][2][3][4][5][6][7][8][9][10][11] In addition to HHV-8, PEL cells are also frequently co-infected by Epstein-Barr virus (EBV). [1][2][3][4][5][6][7][8][9][10]12 The role of viral infection in PEL pathogenesis is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Recently, PEL has been recognized as a unique lymphoma entity based on its distinctive features which include presentation as lymphomatous effusion in the serous body cavities and consistent infection of the tumor clone by human herpesvirus type 8 (HHV-8). [1][2][3][4][5][6][7][8][9][10][11] In addition to HHV-8, PEL cells are also frequently co-infected by Epstein-Barr virus (EBV). [1][2][3][4][5][6][7][8][9][10]12 The role of viral infection in PEL pathogenesis is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] In addition to HHV-8, PEL cells are also frequently co-infected by Epstein-Barr virus (EBV). [1][2][3][4][5][6][7][8][9][10]12 The role of viral infection in PEL pathogenesis is not fully understood. On the one hand, the pathogenetic role of HHV-8 is suggested by the consistency of infection and by the expression of a subset of HHV-8 genes in PEL cells.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 One of the most commonly performed molecular tests is the polymerase chain reaction (PCR) which enables the amplification of specific sequences of nucleic acids from an extremely small amount of genetic starting material. 3 In most laboratories, PCR is usually performed on a variety of fresh specimens including blood, body fluids and tissues.…”
mentioning
confidence: 99%
“…2 Although immunogenotypic studies have confirmed that PEL belongs in all cases to the B cell lineage, Correspondence: G Gaidano, Division of Internal Medicine, Department of Medical Sciences, Amedeo Avogadro University of Eastern Piedmont, Via Solaroli 17, 28100 Novara, Italy; Fax 39 0321 620-421 *These authors contributed equally to this manuscript Received 13 August 1999; accepted 7 October 1999 the overwhelming majority of cases exhibit a non-B, non-T (ie indeterminate) phenotype, lacking expression of surface immunoglobulins and common B cell associated antigens. [1][2][3][4][5][6][7][8][9][10] Recently, the histogenesis of PEL has been the focus of intense research. It is presently thought that PEL originates from a post-germinal center B cell which has undergone preterminal differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] PEL preferentially develops in immunodeficient patients, including both HIV-positive individuals and posttransplant patients, and displays a marked preference for liquid growth in the serous body cavities. [1][2][3][4][5][6][7][8][9][10] The basic pathologic feature of PEL is a net predilection for diffuse spreading along the serous membranes without infiltrative or destructive growth patterns. 2 Although immunogenotypic studies have confirmed that PEL belongs in all cases to the B cell lineage, Correspondence: G Gaidano, Division of Internal Medicine, Department of Medical Sciences, Amedeo Avogadro University of Eastern Piedmont, Via Solaroli 17, 28100 Novara, Italy; Fax 39 0321 620-421 *These authors contributed equally to this manuscript Received 13 August 1999; accepted 7 October 1999 the overwhelming majority of cases exhibit a non-B, non-T (ie indeterminate) phenotype, lacking expression of surface immunoglobulins and common B cell associated antigens.…”
Section: Introductionmentioning
confidence: 99%